Crystal morphology of polyurea on rapid quenching. (20th January 2021) - Chonan, Yuta; Matsuba, Go; Nishida, Koji; Hu, Wenbing
Abstract: Aliphatic polyurea (PUA) is a promising bioengineering plastic that can be prepared from natural resources: castor oil and carbon dioxide. Thus, PUA production could be used to sequester carbon dioxide while producing an environmentally friendly plastic. However, the crystallization behavior of PUA remains unknown. Herein, we reported the detailed analyses of crystallization behavior of PUA. Initially, upon rapid quenching from the melt, the growth of the δ-form crystallizes. Further, 100-nm scaled density fluctuations and the crystal growth process were observed during annealing. The density fluctuations can be assigned to a nodule-type structure. Three melting points after crystallization from the melt were observed by flash differential scanning calorimetry measurements. These three melting peaks were assigned to the melting of PUA nodules, temperature-dependent crystal thickening, and melting of recrystallization crystals from the nodule-type structure. Graphical abstract: Image 1 Highlights: Aliphatic polyurea (PUA) is a promising bioengineering plastic. Crystallization of PUA on rapid cooling reported: PUA crystallizes in the δ-form. On subsequent crystallization above 120 °C, lamellae form. On crystallization below 120 °C, nodule-type structures form. Distinct melting temperatures of nodules, lamellae, and recrystallized regions.